Visualizing MySQL databases using the scalable vector graphics chart creator (SVGCC) - Tan, Gerardo Carlos Roderico Pejo (2011)
Presentation of statistical data graphically is often static-meaning data being visualized through graphs and charts can never be updated once there s change in it (data). Also, these graphs and charts are often presented in raster format, which have reduced quality when the images are resized. This research improves the overall efficiency of the web-based system by Cabazares (2010) that enables any user to visualize data from MySQL databases in an interactive graphical format using Scalable Vector Graphics (SVG). This system enables any user to efficiently visualize and analyze statistical data from a well-known database management system. The system was improved by adding some error-trappers for the bugs that the original system still had, adding the appropriate graphical user interfaces (GUIs) fro its major functions, optimizing the module that processes the generation of the SVG Chart (in terms of speed, size, organization, and readability), adding some new types of graph and evaluating further the system by testing it against some new test databases and using it with the major web browsers of today. The research can be further improved by making the module that generates the SVG Chart more dynamic such that it can cater large data sets, adding more types of graph, and defining more animations for the SVG Chart.